2017
DOI: 10.1007/s00590-017-2073-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk of revision and dislocation in single, dual mobility and large femoral head total hip arthroplasty: systematic review and network meta-analysis

Abstract: Postoperative dislocation is a challenging complication after total hip arthroplasty (THA) that affects patient outcome worldwide. Instability is one of the main complications with rates exceeding 20% in some series. Currently, alternative acetabular components are available with dual mobility (DMTHA) bearing surfaces and larger femoral head size that may reduce the risk of dislocation, yet provide the functional benefit of standard single mobility (STHA) bearing surface THA. However, whether STHA, big femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 39 publications
1
39
0
2
Order By: Relevance
“…THA can effectively relieve pain symptoms and improve the quality of life of patients with hip disease. THA can be performed using a variety of surgical approaches, such as the direct anterior approach (DAA), the anterolateral approach, the lateral approach, and the posterolateral approach (PA) [4][5][6][7][8][9][10] . PA is commonly used because it is relatively simple to operate and is conducive to intraoperative exposure.…”
Section: Introductionmentioning
confidence: 99%
“…THA can effectively relieve pain symptoms and improve the quality of life of patients with hip disease. THA can be performed using a variety of surgical approaches, such as the direct anterior approach (DAA), the anterolateral approach, the lateral approach, and the posterolateral approach (PA) [4][5][6][7][8][9][10] . PA is commonly used because it is relatively simple to operate and is conducive to intraoperative exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The pooled RR (95% CIs) for dislocation in two studies comparing BMI ≥35 vs <35 kg/m 2 A number of previous reviews have attempted to investigate potential risk factors for dislocation in THR, but these have either been based on single or selected risk factors, revision THR, a mixture of both primary and revision THR or were summarised using a narrative approach. [20][21][22][23]25,30,31 Haverkamp and colleagues in their review sought to evaluate the influence of obesity; in pooled analysis of 10 out of 15 studies, they demonstrated obesity (BMI >30 vs <30 kg/m 2 ) to be associated with an increased risk of dislocation. 22 In pooled analysis of 14 studies (of which 12 estimates were actually pooled), Jia and colleagues compared dislocation risk between direct anterior and posterior surgical approaches and reported no statistical significant difference in risk and their estimate was imprecise because of the low event rate.…”
Section: Resultsmentioning
confidence: 99%
“…31 Consistent with our findings of reduced risk of dislocations with dual mobility bearing surfaces (compared with standard bearings) and larger femoral head sizes, a recently published network meta-analysis demonstrated similar findings but was based on primary or revision THRs. 30 To our knowledge, our review represents the first attempt at evaluating and synthesising evidence on the relationships of patient-, surgery-, implant-and hospital-related factors with dislocation risk in one single investigation and in more detail than ever before using a systematic meta-analytic approach.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, as rule of thumb the use of large diameter femoral head could address the problem of instability and mechanical studies have exhibited low dislocation rates with 28 mm femoral head components [13][14][15].This concept does not exhibit complications pertaining to simple implant retention, which solicits attachment through bony press fit, with less wear as the larger joint allowed additional range of motion during dislocation manoeuvers. Pituckanotai, et al, [16] in a recent network meta-analysis recommend dual mobility and big head as safer implants in THA with less risk of dislocation and revision.…”
Section: Discussionmentioning
confidence: 99%